Indicators for best practices in glycemic control in the intensive care unit - Tatiane Lazzarotto Sousa; Eliane Matos; Nádia Chiodelli Salum (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To understand the perception of the nursing team' regarding the management of the intensive glycemic control protocol in order to obtain better practices in glycemic control in the Intensive Care Unit of a University Hospital. Method: A qualitative, convergent care study carried out in an Intensive Care Unit of a university hospital. The data were collected through interviews and workshops and analyzed through thematic analysis. Thirty nursing professionals participated in the study. Results: The importance of the glycemic control protocol which standardizes and guides care was reported by the participants, however they indicated that the used protocol is confusing, difficult to understand and does not include some important guidelines. Restructuring was recommended by adding aspects such as: the desired glycemic value, spaces between glycaemia recording, diet and others; as well as training for its application. Conclusion: The participants recognized the weaknesses of the protocol, and reaffirmed the potentialities of this instrument and defended permanent education as a fundamental factor for the best practices in intensive care.